Non-linear finite element modeling of girth welded pipes under biaxial loading conditions - Lin, Min Ji. (2010)
Offshore pipelines are often installed by the reeling method which introduces large plastic strain in them. These pipelines will also need to be able to withstand loading due to impact, restrained thermal expansion, high differential movements in pipe lines due to seismic ground motion are situations when high strain situations may occur during the operation lifetime of the pipelines. So, it is very important to assess the acceptability of the girth welded pipeline Further the steel pipes are joined by girth welding which may contain both surface and embedded cracks. The pipe lines should have adequate resistance against both crack extension by tearing and unstable fracture during installation as well as during operation. However, common flaw assessment procedures, e.g. BS 7910:2005 [10], are not explicitly developed for such situations with large plastic strains.